2021
DOI: 10.3389/fcell.2021.758400
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Fibroblast Growth Factor Receptor 1-GLI Through AZD4547 and GANT61 Modulates Breast Cancer Progression

Abstract: The underlying mechanism of fibroblast growth factor receptor 1 (FGFR1) mediated carcinogenesis is still not fully understood. For instance, FGFR1 upregulation leads to endocrine therapy resistance in breast cancer patients. The current study aimed to identify FGFR1-linked genes to devise improved therapeutic strategies. RNA-seq and microarray expression data of 1,425 breast cancer patients from two independent cohorts were downloaded for the analysis. Gene Set Enrichment Analysis (GSEA) was performed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…139 FGFR1 has been reported to enhance the expression of vascular endothelial growth factor A through tumor necrosis factor alpha-induced protein 3, thus contributing to breast cancer angiogenesis. 140 By gene set enrichment analysis, Riaz et al 141 found that FGFR1 is strongly correlated with GLI1 family zinc finger 1 (GLI1), a member of the Sonic hedgehog (SHH) pathway, and that the FGFR/GLI1 axis significantly promotes the metastasis of tumor cells. Furthermore, nuclear FGFR1, interacting with RNA-Polymerase II (Pol II) and forkhead box protein A1 (FOXA1), regulates the transcription of target genes, which is a process independent of tyrosine kinase activity and mediates resistance of ER+ breast cancer cells to estrogen inhibitors and fulvestrant.…”
Section: Regulatory Network Of Fgfr1mentioning
confidence: 99%
See 1 more Smart Citation
“…139 FGFR1 has been reported to enhance the expression of vascular endothelial growth factor A through tumor necrosis factor alpha-induced protein 3, thus contributing to breast cancer angiogenesis. 140 By gene set enrichment analysis, Riaz et al 141 found that FGFR1 is strongly correlated with GLI1 family zinc finger 1 (GLI1), a member of the Sonic hedgehog (SHH) pathway, and that the FGFR/GLI1 axis significantly promotes the metastasis of tumor cells. Furthermore, nuclear FGFR1, interacting with RNA-Polymerase II (Pol II) and forkhead box protein A1 (FOXA1), regulates the transcription of target genes, which is a process independent of tyrosine kinase activity and mediates resistance of ER+ breast cancer cells to estrogen inhibitors and fulvestrant.…”
Section: Regulatory Network Of Fgfr1mentioning
confidence: 99%
“…FGFR1 has been reported to enhance the expression of vascular endothelial growth factor A through tumor necrosis factor alpha‐induced protein 3, thus contributing to breast cancer angiogenesis 140 . By gene set enrichment analysis, Riaz et al 141 . found that FGFR1 is strongly correlated with GLI1 family zinc finger 1 (GLI1), a member of the Sonic hedgehog (SHH) pathway, and that the FGFR/GLI1 axis significantly promotes the metastasis of tumor cells.…”
Section: Fgfr Is Involved In Human Tumorsmentioning
confidence: 99%
“…32 Similarly, overexpression of BST-2 has potential implications in breast cancer onset, 33 while FGFR1 overexpression substantially interferes with endocrine therapy, fostering resistance. 30,31,34 Another gene, SNRPD1, augments tumorigenicity via cell cycle modulation. 35 However, most prognostic models utilize these genes singularly, focusing on a specific gene set.…”
Section: Discussionmentioning
confidence: 99%
“…This includes UNC5B, which, when overexpressed, amplifies breast cancer cell proliferation, consequently dampening prognosis 32 . Similarly, overexpression of BST‐2 has potential implications in breast cancer onset, 33 while FGFR1 overexpression substantially interferes with endocrine therapy, fostering resistance 30,31,34 . Another gene, SNRPD1, augments tumorigenicity via cell cycle modulation 35 .…”
Section: Discussionmentioning
confidence: 99%